PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO PEMBELAJARAN PADA MATA PELAJARAN IPA DALAM IMPLEMENTASI KURIKULUM 2013 - Muhammad Ali (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
The learning process plays an important role in producing the quality of graduates. The main thing that must be considered by education stakeholders is to create quality learning. Many aspects can affect the quality of education, including: qualified and qualified teachers with qualifications mandated by teacher and lecturer laws, use of interesting and varied teaching methods, positive learners' learning behaviors, learning conditions and atmosphere which is conducive to learning and the use of appropriate learning tools to support the learning process. Student achievement data of SMP Negeri 1 Pulau Sembilan Year Lesson 2016/2017 on science subjects from subject Teachers found that 42% of students have enough value, 33% students have good grades and 25% of students have very good grades. The results of the interview to the students that 70% of students feel constrained when understanding the material, while 95% of students want the teaching-learning materials that can support the understanding of science materials. The purpose of research and development are: (1) developing teaching-learning materials based on learning videos on science subjects, (2) students' learning outcomes after learning process using instructional materials based on learning videos on science subjects. Research and development methods used Research and Development (R & D). Development is carried out with reference to the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model proposed by Russell and Molenda. The validation of instructional materials based on learning videos on these subjects is assessed on the feasibility of content, presentation, and language by expert, teacher, and peer review validation. Based on the validation of the content feasibility, presentation, and instructional materials based on learning videos on science subjects, it is considered feasible to be used and implemented in SMP Negeri 1 Pulau Sembilan Kotabaru Regency. Student learning outcomes were analyzed by parametric test using wilcoxon test which was processed using IBM SPSS Statistic 22 software. The result of research and development were (1) instructional material based on learning video on science subjects developed using ADDIE model include Analyze, Design, Development, Implementation, and Evaluation, (2) student learning outcomes after following the learning process usinginstructional materials based on learning video on science subjects experience a significant improvement. Increased student learning outcomes seen from the p-value of -4.462 below (<0.05). Keywords: Learning-Based Teaching Materials, Science Lessons, ADDIE